La costruzione della memoria - Di Martino, Carmine (Bollettino Filosofico, 2016)
How can we make use of our past and, therefore, how can talk about memory in its full sense? This work aims to identify the constitutive elements of the experience of memory, understood as the possibility of freely and actively using our past - that is, to use it in a different way from infants and animals -, first through the analysis of the Husserlian, phenomenological studies dedicated to memory, and then of experimental psychology. To this purpose, it is crucial the notion of language, not so much conceived of as a predicative structure, but rather in its most originary meaning: as nomination, signification, i.e. symbolized possession of ideal meanings. To remember we need to talk, to have access to the linguistic translation of experience and to the dimension of the "meaning already known". Without being aware of meaning we can not build memories at all.